Doc. PaedDr. Jiřina Holinková, CSc. Historian and university teacher witnessed by her contemporaries - Kollerová, Michaela (Theatrum historiae, 2014)
This study looks at the life, scientific and pedagogical activity of doc. PaedDr. Jiřina Holinková, CSc. (1921–2005), a historian, who worked for more than fourty years at the Department of History at the Faculty of Arts, Palacký University in Olomouc. The author of this study also tries to describe the personality of doc. Holinková. One of the methods used during the research was oral history, therefore the first part of this study is focused on using this method and its importance for this specific research.